PERBANDINGAN HASIL BELAJAR MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD, TAI DAN TGT - Susanto, Doni (STKIP PGRI NGAWI, 2014)
Abstract : This problem aims to determine whether there are differences in mathematics learning outcomes on the subject of figures with flat sides between students taught using cooperative learning model Student Team Achievement Division (STAD), Team Assisted Individualization (TAI) and Teams Games Tournament (TGT). This problem is a quantitative problem with experimental approaches. Samples were students of VIII F, VIII Â G, VIII H class on the second semester of SMP 2 Geneng in academic year 2013/2014. Sampling technique using simple random sampling. Outcomes data collection techniques that students learn mathematics by using test method and documentation method. Hypothesis test were analyzed using One Way Analysis of Variance (One Way ANOVA).Based on the results of this problem concluded that there are differences in mathematics learning outcomes of students who are taught with cooperative learning model STAD, TAI and TGT on the subject of figures with the flat side on the second semester of eighth grade SMP 2 Geneng in academic year 2013/2014. This is showed by One Way Analysis of Variance (One Way ANOVA) with Î± = 5%, the numerator df = 2 and the denominator df = 80 obtained Ftable = 3, 110 so Fobs > Ftable is 12,899 > 3,110 and the average value of the final test 75.231 for STAD class, 80.071 for TAI class and 74.172 for TGT class. Mathematics learning outcomes of students who are taught with cooperative learning model TAI is the best result of the most studied mathematics on the subject of figures with flat side compared with the outcomes of learning mathematics students taught with cooperative learning model STAD and TGT. It can be seen in multiple comparison test with the Scheffe method with Î± = 5% and 2FÎ± = 6.220. Comparative results obtained TAI vs. STAD class Fij (14,649) > 2FÎ± (6,220), the learning outcomes are taught mathematics by TAI learning model is better than taught by STAD models, comparative results obtained TGT Vs STAD classes Fij (0.713) < 2FÎ± (6,220), the learning outcomes of students who are taught mathematics STAD model is as good as TGT taught using learning model and comparative results obtained TGT Vs TAI class Fij (22,995) > 2FÎ± (6,220), the learning outcomes of students who are taught mathematics learning model TAI better than the model of learning taught by TGT. Keywords: Comparison, Results Math Learning, Cooperative Learning Model, STAD, TAI, TGT.